Makna Ahlul Bait dalam Al-Qur’an Menurut Ulama Tafsir Nusantara - Muhammad Suib (Lembaga Yasin AlSys, 2024)
In terms of Ahlul Bait, it is forbidden to receive zakat and alms because of their kinship with the Prophet, namely the descendants of the Prophet, his wives, and all Muslims and Muslim women from the descendants of 'Abdul Muththalib, namely the Bani Hayim. Therefore, the Ahlul bait includes the family of Ali bin Abi Talib, the family of Ja'far bin Abi Talib, the family of 'Aqil bin Abi Talib, and the family of 'Abbas bin 'Abdul Muttalib. They were all from Bani Hashim. This study is qualitative research and the method used is the library method (Library Research). Research that collects data from written works, in the form of books, tafsir books, and literature related to the meaning of Ahlul Bait in the Koran. In its development, the descendants of the Prophet in Arab society were known as a group that called itself the